2007
DOI: 10.1074/jbc.m701415200
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Acclimation in Chlamydomonas reinhardtii

Abstract: Both prokaryotic and eukaryotic photosynthetic microbes experience conditions of anoxia, especially during the night when photosynthetic activity ceases. In Chlamydomonas reinhardtii, dark anoxia is characterized by the activation of an extensive set of fermentation pathways that act in concert to provide cellular energy, while limiting the accumulation of potentially toxic fermentative products. Metabolite analyses, quantitative PCR, and high density Chlamydomonas DNA microarrays were used to monitor changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
156
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(161 citation statements)
references
References 77 publications
(104 reference statements)
4
156
1
Order By: Relevance
“…3A). It has been reported previously that metabolite levels of fermentative products and transcript levels of genes of fermentative pathways increase during anaerobic cultivation in the dark (21). Recent metabolome studies have dem- (38).…”
Section: Two-dimensional Gcxgc-tofms Analysis During H 2 Production Rmentioning
confidence: 99%
See 3 more Smart Citations
“…3A). It has been reported previously that metabolite levels of fermentative products and transcript levels of genes of fermentative pathways increase during anaerobic cultivation in the dark (21). Recent metabolome studies have dem- (38).…”
Section: Two-dimensional Gcxgc-tofms Analysis During H 2 Production Rmentioning
confidence: 99%
“…When the culture is subjected to sulfur limitation but still aerobic, starch, fatty acid, and lipid synthesis are strongly induced. In contrast when anaerobic conditions are established, it seems that pyruvate is mainly used for amino acid synthesis and fermentative pathways to control the cellular redox balance (21,24,25,46) (Figs. 2 and 4 -6).…”
Section: Two-dimensional Gcxgc-tofms Analysis During H 2 Production Rmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteomic studies have suggested that the Pat1-Ack2 pathway is localized to mitochondria (note that phosphotransacetylase is designated Pat in Chlamydomonas), and the Pat2-Ack1 pathway is localized to chloroplasts (13,17). Acetate has been found to be one of the major fermentative products excreted by Chlamydomonas during growth under dark, anoxic conditions, and ACK1, ACK2, PAT1, and PAT2 transcript levels are increased, in agreement with a role for the Pat-Ack pathway in acetate production (18). The ack1 and pat2 mutants were the most vulnerable to anoxia, and strains could not be recovered after a 24-h exposure to anoxia (19).…”
mentioning
confidence: 55%